A Tubular Linear-Rotary Generator With Dual Stators for Direct Drive Wind-Wave Complementary Energy Generation Platform - Jing Zhang; Minshuo Chen; Yulei Liu (IEEE Access)
So as to the efficient and low-cost utilization of offshore renewable energy, a novel direct-drive wind-wave complementary energy generation (D-D WWCEG) platform based on a tubular permanent magnet (PM) linear-rotary generator (TPMLRG) with dual stator is proposed in this study. According to the demand of the load and the energy storage, the D-D WWCEG system has stable output power, few non-operating hours and good anti-disturbance performance under different sea conditions by energy storage. Firstly, combine the design steps of traditional motors, the design process of TPMLRG is given, and the key parameters of linear power generation module (LPGM) and rotating power generation module (RPGM) are optimized by combining the finite element analysis (FEA) and multi-objective optimization method. The magnet field, thermal distribution and the magnetic properties of the PMs are analyzed by multiple coupled models. Secondly, the direct circuit - direct circuit converter (DC/DC) circuit for energy storage is designed and tested, the results show that under a wide fluctuation input voltage, a constant charging current of 0.2A is obtained for the lithium battery. Finally, based on the optimized parameters of TPMLRG, the energy conversion efficiencies of LPGM and RPGM are respectively obtained as 61.0% and 49.8%.